2023
DOI: 10.3390/foods12020422
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Seafood Side-Streams and Residuals into Valuable Products

Abstract: Seafood processing creates enormous amounts of side-streams. This review deals with the use of seafood side-streams for transformation into valuable products and identifies suitable approaches for making use of it for different purposes. Starting at the stage of catching fish to its selling point, many of the fish parts, such as head, skin, tail, fillet cut-offs, and the viscera, are wasted. These parts are rich in proteins, enzymes, healthy fatty acids such as monounsaturated and polyunsaturated ones, gelatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 189 publications
0
20
0
Order By: Relevance
“…The biorefinery approach involving multiple processes as a circular economy business model aims to total utilization of the raw material at higher efficiency at reduced production costs. This ensures sustainability and economic benefits besides protecting the environment. ,, The bioconversion of feedstock on a zero-waste strategy involves essentially three steps, known as “3R”, namely, “reuse-remake-recycle” . A marine biorefinery envisages integration of green methods for recovery of various ingredients present in marine resources, essentially through a circular blue economy framework .…”
Section: Marine Biorefinery For Integrated Green Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…The biorefinery approach involving multiple processes as a circular economy business model aims to total utilization of the raw material at higher efficiency at reduced production costs. This ensures sustainability and economic benefits besides protecting the environment. ,, The bioconversion of feedstock on a zero-waste strategy involves essentially three steps, known as “3R”, namely, “reuse-remake-recycle” . A marine biorefinery envisages integration of green methods for recovery of various ingredients present in marine resources, essentially through a circular blue economy framework .…”
Section: Marine Biorefinery For Integrated Green Processingmentioning
confidence: 99%
“…Their implementation, however, requires expertise in all stages of manufacturing in addition to a clear vision of all raw materials, residues, and products. Ocean-based industries are adopting new sustainable production models, particularly biorefineries, which are effective for converting low-value biomass into commercially relevant byproducts. …”
Section: Marine Biorefinery For Integrated Green Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained in the present study for the TAC in the extracts were higher than those reported by Muangrat et al (2018) for Thai purple corn cob extracts processed by ultrasound (ultrasonic probes, 20 kHz / 500 W / 30 min), and by Itthisoponkul et al (2018) for aqueous extracts of Thai purple corn cob processed by HIP (200 MPa / 25 °C / 15 minutes). According to Dukić et al (2022), ultrasonic extraction through ultrasonic probes implies direct contact of the probe with the analyte and constant cooling of the sample, therefore, this can lead to the degradation of the thermolabile components and thus affect the reduction of the content of valuable molecules; while in high isostatic pressure, the pressure transfer being simultaneous and uniform at all points of the sample implies induced damage to the cell matrix, greater permeability and consequently the release of bioactive compounds bound to the matrix (Siddiqui et al, 2023). On the other hand, Tatiane et al (2023) mention that the high pressure also allows the solvent to remain in a liquid state and above its boiling point, being sufficiently capable of helping it penetrate the plant matrix and achieve greater extraction.…”
Section: Effect Of Hip On the Tac Of Purple Corn Cob Extractsmentioning
confidence: 99%
“…One focus has been peptides from marine sources (fish, shellfish, and invertebrates) with antioxidant activity [7][8][9][10]. Antioxidant peptides have an essential role in inhibiting oxidation and scavenging free radicals.…”
Section: Introductionmentioning
confidence: 99%